Pengaruh Pendidikan dan Pelatihan Terhadap Prestasi Kerja Karyawan Bagian Fixed Phone Sales pada PT.Telekomunikasi.Tbk Denpasar - Pratama Putra, I Gede Gandi; Yuniari, Made (E-Jurnal Manajemen; Vol 2 No 7 (2013), 2013)
This study aims to determine the influence of education and training on workers’ job performance. This study is done at PT. Telekomunikasi, Tbk with 65 respondents. Data Analysis technique used is multiple linear regression. The result of this study are education and training influence significantly either simultanesously or partially as well as training is  the dominant variables influence on workers’ job performance.   Keywords: Education, training, job performance